Abalou Bangu! A fábrica Bangu e a República nascente (1889-1914) - Freitas, Adriana Oliveira de (2005)
This research analyses the role of "Companhia Industrial do Brasil", popularly known by "Fabrica Bangu".It was very important in the industrialization and building process of the urbarn enviromment in Brazil, exactly at Distrito Federal, during the years of 1889 to 1914. It concentrates on the urbanization and industrialization proposal, on the idea of progress and modernization and also on the changing of the concept "work" promoted by the recent Republic. Then, we could notice that "Fabrica Bangu" reflected everything that the Republic was trying to implemet at the "Capital Federal". The factory's symbols, memories and photographs were also analysed. They were useful on the comprehension of the factory's image of itself, for example, how it wanted to be seen by the society and how its staff used to see it.